Mesenchymal Progenitor Regulation of Tooth Eruption: A View from PTHrP. (February 2020) - Nagata, M.; Ono, N.; Ono, W.
Tooth eruption is a unique biological process by which highly mineralized tissues emerge into the outer world, and it occurs concomitantly with tooth root formation. These 2 processes have been considered independent phenomena; however, recent studies support the theory that they are indeed intertwined. Dental mesenchymal progenitor cells in the dental follicle lie at the heart of the coupling of these 2 processes, providing a source for diverse mesenchymal cells that support formation of the highly functional tooth root and the periodontal attachment apparatus, while facilitating formation of osteoclasts. These cells are regulated by autocrine signaling by parathyroid hormone–related protein (PTHrP) and its parathyroid hormone/PTHrP receptor PPR. This PTHrP-PPR signaling appears to crosstalk with other signaling pathways and regulates proper cell fates of mesenchymal progenitor cell populations. Disruption of this autocrine PTHrP-PPR signaling in these cells leads to defective formation of the periodontal attachment apparatus, tooth root malformation, and failure of tooth eruption in molars, which essentially recapitulate primary failure of eruption in humans, a rare genetic disorder exclusively affecting tooth eruption. Diversity and distinct functionality of these mesenchymal progenitor cell populations that regulate tooth eruption and tooth root formation are beginning to be unraveled.